The power-to-weight relationships and efficiency improvements of olympic champions in athletics, swimming and rowing - Stefani, R. (International Journal of Sports Science and Coaching, 2014)
The goals of this article are to provide power-to-weight relationships, changes in which are predictive of changes in performance for athletics (running, jumping and throwing), for swimming and for rowing. Also this article will estimate improvements in the efficient application of power exhibited by Olympic champions in those same events over the span of the modern Games. For the former goal, the ergometer power output of an athlete, measured under laboratory conditions, is modeled in terms of training, lean body mass and a cranking term as reflected in upper arm and shoulder volume. The laws of physics are used to relate event performance to efficiency and to a power-to-weight relationship specific to each event, with both efficiency and power-to-weight raised to an exponent specific to each event. The power-to-weight relationship, in turn, depends on training and on a lean-to-total body mass relationship. The ratios of female/male Olympic championship performances are then used since significant differences may be observed. Further, the relative need for upper arm and shoulder strength may be estimated for throwing and rowing. Physiological values estimated from the ratio of female/male Olympic winning performances in athletics and swimming compare closely with actual physiological relationship, validating that analysis. Rowing relationships were also validated from performance-physiological considerations. Having validated the analysis, reliable relationships then follow between changes in the power-to-weight ratio and event performance. As to the latter goal, the observed mean improvement in winning performance per Olympiad is found for each event, leading to estimated efficiency improvement per Olympiad.